2015
DOI: 10.1007/s00784-015-1619-9
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of resin-bonded fixed partial dental prostheses made with metal alloys

Abstract: ObjectivesThe purpose of this study was to evaluate the clinical performance of resin-bonded fixed partial dental prostheses (RBFPDPs) made with metal alloys.Materials and methodsThe retention of 311 RBFPDPs from 226 patients fabricated from 1983 to 2013 using an adhesive resin was clinically evaluated. Partial or complete debonding of the RBFPDP or framework fracture was considered a treatment failure. All data were obtained from clinical examinations, and missing data were censored at the date of the last av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…The long-term prognosis of restorations retained with composite luting cement and SB have been reported, with a survival rate of SB estimated to be 84.6% at 5 years, 68.5% at 10 years, 58.8% at 15 years, and 35.2% at 20 to 25 years. 23 The results from the present study showed a cumulative survival rate of 94.9% at 5 years, 91.8% at 10 years, and 78.4% at 15 years. The improvement may have been that the patient's age and the operating dentist influenced the prognosis of the restorations.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…The long-term prognosis of restorations retained with composite luting cement and SB have been reported, with a survival rate of SB estimated to be 84.6% at 5 years, 68.5% at 10 years, 58.8% at 15 years, and 35.2% at 20 to 25 years. 23 The results from the present study showed a cumulative survival rate of 94.9% at 5 years, 91.8% at 10 years, and 78.4% at 15 years. The improvement may have been that the patient's age and the operating dentist influenced the prognosis of the restorations.…”
Section: Discussionsupporting
confidence: 50%
“…The improvement may have been that the patient's age and the operating dentist influenced the prognosis of the restorations. 23,24 Accordingly, the favorable results obtained in the present study may have been because most of the treatment was provided by a dentist with over 15 years of clinical experience. However, considering that the results of the examination of the long-term prognosis for ZPC did not vary much from those of existing reports, it seems more likely that the influence of the adhesive resin cement used was greater than that of the years of experience of the dentist.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A total of 780 papers were identified, 753 of which were excluded after a review. Two papers were also included based on a non-electronic search, leaving a total of 29 articles for inclusion in this review [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the 15-year cumulative success/survival rates were 53.4/66.5% for the RBFDP group and 59.2/61.6% for the FDP group, indicating no significant difference. Curiously, Tanoue [ 36 ] evaluated the long-term clinical performance of several types of RBFDPs composed of metal alloys; the maximum observation period was 28.8 years, and the mean observation time was 13.9 years. In that study, 311 RBFDPs—both surface-retained (i.e., two-retainer) and combination type (i.e., retainer/full coverage crown)—from 226 patients were evaluated.…”
Section: Resultsmentioning
confidence: 99%